Integrated motor drives - Deng, Xu; Mecrow, Barrie (IET energy engineering series, 2022)
Optimisation of electric drives for machines and EV requires considering the components as a whole. Integrated systems can be smaller, have greater flexibility, lower cost and higher power density. This book presents recent research and trends in integrated electrical motor drive technology.